Multicentre analysis of current strategies and outcomes in open aortic arch surgery: heterogeneity is still an issue - Urbanski, Paul; Kallenbach, Klaus (European journal of cardio-thoracic surgery, 2016)
AbstractOBJECTIVES. The study was conducted to evaluate, on the basis of a multicentre analysis, current results of elective open aortic arch surgery performed